Unusual Cause of Knee Locking - Gazi Huri; Omer Sunkar Biçer (Case Reports in Orthopedics)
We report a case of partial intrasubstance tear of popliteus tendon as an unusual cause of pseudolocking of the knee. A 13-year-old semiprofessional soccer player applied to our clinic with a locked right knee in spite of the therapy applied (cold pack, NSAID, and immobilization) in another institution 20 days after the injury. Significant extension loss was observed in his right knee with 30∘–90∘ ROM. Magnetic resonance imaging (MRI) and arthroscopy confirmed the intrasubstance tear of popliteus tendon and synovitis. The ruptured part of the tendon was debrided, and the inflammatory tissue around the tendon, which may lead to pseudolocking, was gently removed with a shaver in order to regain the normal ROM. The patient was discharged with full ROM and weight bearing first day after the surgery. To our knowledge, this is the first case demonstrating intrasubstance tear of popliteus tendon causing pseudolocking of the knee.